(untitled) - Sjaastad, Ottar (CIC Edizioni Internationali)

Tension-type headache: one or more headaches? (2011)
In this context, the focus will be on the homogeneity of tension-type headache (T-TH): is it a disease? Or: is it more likely to be a syndrome? A multiplicity of disorders from as drastically different fields of medicine as disorders caused by environmental gases, intra-psychic conflicts, and nuchal/cervical disorders can putatively fake T-TH. T-TH is in all probability a conglomerate of disorders and not one solid, homogeneous disorder.